Opini dan Analisis Program Layanan Informasi di Perpustakaan dengan Metode Jarak Jauh (Studi Kasus Layanan Informasi Menggunakan Aplikasi Imobile Ipusnas) - Mardiyanto, Verry (TIK ILMEU : Jurnal Ilmu Perpustakaan dan Informasi, 2018)
This study discusses about opinion and analysis of information service program in library using online method, (a case study of information service using Ipusnas Imobile Application). Qualitative descriptive approach was used in this study, and observation to iPusnas application directly was conducted for data gathering. We tried to answer how online library information service using iPusnas application was utilized, how the process flow of information service is, and what advantage and disadvantage iPusnas application has as our research problems. We found that this application is applicable to all people in general, whether they are old, young or have little capability in using the application as long as they have understood information technology. Moreover, this application can encourage millennial generationâs reading interest as they spend most of their time in using information technology devices. This application is still in startup form and need to be developed more in its loading process, features, book collection, and bug improvement to support digital library.